Proceedings of the International Conference on Applied Science and Technology on Social Science 2022 (iCAST-SS 2022) 2022
DOI: 10.2991/978-2-494069-83-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception of ESP Teachers’ Performance at Indonesian State Polytechnics

Abstract: There are two divisions of ESP (English for Specific Purposes) teachers at the early established state Polytechnics throughout Indonesia: first and secondgeneration teachers. The first generation participated in the Polytechnic Education Development Centre (PEDC) from 1987-1994, and the second generation of ESP teachers never participated in this training program. There hasn't been any investigation into the performance of these two groups of teachers to identify the impact of the PEDC training on their perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A large number of students were participated, and data was gathered using a variety of questionnaires. The findings revealed that both generations had distinct skills in many areas such as need analysis, teaching technique, teaching content, teaching medium, and assessment (Sofa, Mariam, & Saputro, 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…A large number of students were participated, and data was gathered using a variety of questionnaires. The findings revealed that both generations had distinct skills in many areas such as need analysis, teaching technique, teaching content, teaching medium, and assessment (Sofa, Mariam, & Saputro, 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Furthermore, there are some scholars investigating students' needs in ESP courses, especially in students of Higher Education. ESP course evaluation was carried out for the students of non-English major (Jaya & Subiyanto, 2017;Asmat el al., 2021;Sikumbang & Dalimunte, 2021;Satriani & Resmini, 2021;Sofa et al, 2022, Solihah et al, 2023. Those previous studies concerned the students' perspectives toward the ESP materials evaluation relating to the major studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Satriani and Resmini (2021) showed that the ESP materials developed the students' confidence to fulfill the tasks in the textbook. Sofa et al (2022) showed that ESP Teachers' performances in Business major had their own strength to find out students' need for analysis, teaching method, teaching materials, teaching media, and assessment.…”
Section: Introductionmentioning
confidence: 99%